Waterfowl production from winter wheat fields in North and South Dakota. Issue 1 (28th September 2015) - Skone, Brandi R.; Rotella, Jay J.; Walker, Johann
ABSTRACT: The Prairie Pothole Region (PPR) of North America produces more than 50% of North America's upland‐nesting ducks. With the recent increase in economic value of some cash‐crops and the potential to lose productive nesting habitat enrolled in the Conservation Reserve Program (CRP), there has been interest in evaluating the efficacy of alternative farming practices to provide additional breeding habitat for waterfowl. We evaluated and compared daily survival rates (DSR) of duck nests ( Anas spp.) in winter wheat with those in perennial cover. We also examined the number of hatched nests/ha in each habitat and compared them to estimates in spring wheat to put habitat‐specific estimates of nest survival in perspective. We monitored 1, 195 nests in winter wheat and 3, 147 in perennial cover in North and South Dakota on 13–19, 10.36‐km 2 sites each year from 2010 to 2012. In 2010, we also monitored 75 nests in spring wheat. We used an information‐theoretic approach to develop and evaluate a set of competing models based on plausible and previously established covariates affecting nest survival. Across all species, nest survival was at least as high in winter wheat as in perennial cover, and for northern pintails and mallards, estimated nest survival rates were greater in winter wheat. Nest survival also varied by year and study area, was positively related to nest age, and was negatively related to the number of wetland basins, the proportion of cropland in the landscape, and vegetation density. Density of hatched nests in perennial cover (0.14/ha) was on average twice as high as nests in winter wheat fields (0.07/ha), which was in turn 4 times higher than estimates for spring wheat fields (0.02/ha). Our results provide evidence that winter wheat could be a useful tool for wildlife managers seeking to add productive nesting habitat in landscapes under intensive crop production. © 2015 The Wildlife Society.